Biallelic loss of function variants in COASY cause prenatal onset pontocerebellar hypoplasia, microcephaly, and arthrogryposis. (December 2018) - Dijk, Tessa; Ferdinandusse, Sacha; Ruiter, Jos; Alders, Mariëlle; Mathijssen, Inge; Parboosingh, Jillian; Innes, A.; Meijers-Heijboer, Hanne; Poll-The, Bwee; Bernier, Francois; Wanders, Ronald; Lamont, Ryan; et al.
Abstract Pontocerebellar hypoplasia (PCH) is a heterogeneous neurodegenerative disorder with a prenatal onset. Using whole-exome sequencing, we identified variants in the gene Coenzyme A (CoA) synthase (COASY) gene, an enzyme essential in CoA synthesis, in four individuals from two families with PCH, prenatal onset microcephaly, and arthrogryposis. In family 1, compound heterozygous variants were identified inCOASY : c.[1549_1550delAG]; [1486-3 C>G]. In family 2, all three affected siblings were homozygous for the c.1486-3 C>G variant. In both families, the variants segregated with the phenotype. RNA analysis showed that the c.1486-3 C>G variant leads to skipping of exon 7 with partial retention of intron 7, disturbing the reading frame and resulting in a premature stop codon (p.(Ala496Ilefs*20)). No CoA synthase protein was detected in patient cells by immunoblot analysis and CoA synthase activity was virtually absent. Partial CoA synthase defects were previously described as a cause of COASY Protein-Associated Neurodegeneration (CoPAN), a type of Neurodegeneration and Brain Iron Accumulation (NBIA). Here we demonstrate that near complete loss of function variants inCOASY are associated with lethal PCH and arthrogryposis.